Cutaneous atypical mycobacteriosis - Sultana, Razia; Wahiduzzaman, Md (Bangladesh Medical Journal Khulna, 2018)
Mycobacterium chelonae rarely causes skin infection, usually after minor trauma. A 44 year old lady complained of skin rashes on left lateral back above the flank for 6 months. Physical examination showed multiple papulo-pustular eruption and sinus on an erythematous base. Repeated histopathological examination did not give any authentic clue. Ultimately on clinical ground and therapeutic trial, it was diagnosed as rapidly growing atypical mycobacterial (Mycobacterium chelonae) infection. Bang Med J (Khulna) 2017; 50 : 44-45